The maternal prepregnancy body mass index and the risk of attention deficit hyperactivity disorder among children and adolescents: a systematic review and meta-analysis - Ensiyeh Jenabi; Saied Bashirian; Salman Khazaei; Zohreh Basiri (Korean Pediatric Society, 2019)
Background Attention deficit hyperactivity disorder (ADHD) symptoms have a major impact on individuals, families, and society. Therefore identification risk factors of ADHD are a public health priority. Purpose This is meta-analysis evaluated the association between maternal prepregnancy body mass index and the risk of ADHD among the resulting offspring. Methods The search identified studies published through December 2018 in the PubMed, Web of Science, and Scopus databases. The odds ratios (ORs) or hazard ratios (HRs) with 95% confidence intervals (CI) extracted from eligible studies were used as the common measure of association among studies. Results A significant association was found between overweight women and the risk of ADHD among children with the pooled HR and OR estimates (HR, 1.27 and 95% CI, 1.17-1.37; OR, 1.28 and 95% CI, 1.15-1.40, respectively). This association was significant between obese women and the risk of ADHD among children and adolescents with the pooled estimates of HR and OR (HR, 1.65 and 95% CI, 1.55-1.76; OR, 1.42 and 95% CI, 1.23-1.61). Conclusion The current epidemiological studies present sufficient evidence that prepregnancy overweight and obesity are significantly associated with an increased risk of ADHD among children and adolescents. These findings provide a new approach to preventing ADHD by controlling weight gain in the prenatal period, which should be considered by policymakers.